(untitled) - Du Toit, Cara

Genotype-by-environment interaction analysis on bud break dynamics, yield potential and fruit quality of diverse apple (Malus domestica) trees in contrasting environments (Stellenbosch : Stellenbosch University, 2025)
Thesis (MScAgric)--Stellenbosch University, 2024.